Iberian species of the subgenus Bunobus De Ley, Siddiqi & Boström, 1993 (Nematoda, Rhabditida, Cephalobidae), with description of Pseudacrobeles (Bunobus) rotundilabiatus sp. n. and comments on the subgenus - Abolafia, Joaquín; Peña-Santiago, Reyes (Zootaxa, 2013)
Two Iberian species of the subgenus Pseudacrobeles (Bunobus), one new and another known, collected from natural areas are described and illustrated, including morphometric and LM photographs. Pseudacrobeles (Bunobus) rotundilabiatus sp. n. is characterized by a body length of 624–805 μm long in females and 670–714 μm in males, lateral field with three incisures terminating gradually near the phasmid, lip region continuous with the adjacent body, subdorsal and subventral lips rounded, lateral lips reduced, stoma 13–17 μm long, pharyngeal corpus 3.0–4.3 times as long as isthmus, V = 63–74, spermatheca 22–62 μm long, postvulval sac 1.0–2.0 times the body diameter in length, female tail conical elongated (59–83 μm, c = 9.7–11.6, c' = 4.5–6.8) ending in a lanceolate mucro slightly tuberculate proximally, male tail conical (38–40 μm long, c = 10.1–16.8, c' = 3.9), spicules 25 μm long, and gubernaculum 14 μm long. Pseudacrobeles (Bunobus) pseudolatus is re-described based on type specimens. In addition, an emended diagnosis is provided for the subgenus as well as an updated list of species, a compendium of their morphometrics and a key to their identification.